Politikai szocializáció Magyarországon a kilencvenes években - Csákó, Mihály; Berényi, Eszter; Bognár, Éva; Tomay, Kyra (Szociológiai Szemle, 2024)
This is the first publication in Hungarian o f the results of the series of research done by the students o f sociology o f ELTE University on the basis of three data collections among seventh-form pupils of primary schools in the 90s. The research was focused on the initial degrees of political interest and on its specific determinants, mostly on the basis of Annick Percheron's theory. We have found some difference in the degree of interest (measured by direct questioning and edited variables) between boys and girls, and between the pupils of schools in housing estates/slum areas/elite ones. During the 90s political interest, and political activity in particular, were decreasing among the young teenagers. The political interest of parents seems to be the most decisive determinant of all. Attitudes towards differentness are strongly positive in respect of the great Western nations, they are often negative towards Gypsies, but they are only weakly related to the other variables of political socialisation. The experiences of the research correspond to Pecheron's hypothesis, that the process of political socialisation goes parallel to the fullest possible integration into the adult world.